Construction of One- Child Women Understanding Of Childbearing Challenges (Participants: One- Child Women of Ahvaz) - Jahangir Jahangiri; habib ahmadi; mansour tabiee; hossein moltafet (توسعه اجتماعی)
The family as the foundation of society, throughout history, has been changed under the influence of various economic and social Evolutions. Certainly Iranians today family issues are different from fifty or one hundred years ago. During recent decades the trend of population growth and childbearing has led some families to have one child. This study has tried to explore the actions of one-child women of Ahvaz, and has recognized challenges of participants in relation to family and parenting that leads to this behavior. To achieve this goal, qualitative methodology and grounded theory have been used. Twenty women, who had just one child, were selected through purposive and theoretical sampling. Data were collected through in-depth interviews. Data analysis was done by open, axial and selective coding. The results included 17 sub-categories, 6 main categories and the core category of “facing the difficult challenges of childbearing”. Results show that the lack of adequate protection of women and families and not having enough time due to work or study are conditional challenges for childbearing. Women facing with these challenges in the context of the financial and housing problems and previous unpleasant experience of large size family, and risk of Intervention of the social climate and high cost of raising children, chose the one-child strategy.